The use of bovine colostrum in sport and exercise - Davison, G. (Nutrients, 2021)
There has been a great deal of interest in bovine colostrum within sports nutrition over the last 25 years. Studies have investigated the effects on body composition, physical performance, recovery, gut damage and permeability, immune function, and illness risk. This narrative review considers available evidence in each of these areas. Although some studies have shown protection against performance decrements caused by periods of intensified training, there is limited evidence for effects on body composition and physical performance. There is stronger evidence for benefit on gut permeability and damage markers and on immune function and illness risk, especially during periods of intensified training. The balance of available evidence for gut permeability and illness risk is positive, but further research is required to fully determine all mechanisms responsible for these effects. Early suggestions that supplementation with bovine colostrum products could increase systemic IGF-1 levels are not supported by the balance of available evidence examining a range of doses over both short- and long-term periods. Nevertheless, dose-response studies would be valuable for determining the minimum efficacious dose, although this is complicated by variability in bioactivity between products, making any dose-response findings applicable only to the specific products used in such studies.